2013
DOI: 10.1371/journal.pone.0053310
|View full text |Cite
|
Sign up to set email alerts
|

Exome Capture Sequencing of Adenoma Reveals Genetic Alterations in Multiple Cellular Pathways at the Early Stage of Colorectal Tumorigenesis

Abstract: Most of colorectal adenocarcinomas are believed to arise from adenomas, which are premalignant lesions. Sequencing the whole exome of the adenoma will help identifying molecular biomarkers that can predict the occurrence of adenocarcinoma more precisely and help understanding the molecular pathways underlying the initial stage of colorectal tumorigenesis. We performed the exome capture sequencing of the normal mucosa, adenoma and adenocarcinoma tissues from the same patient and sequenced the identified mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…Excluding this hypermutated HGCA, a total of 772 somatic non-silent mutations (752 non-synonymous SNVs and 20 indels) (average: 70.2, range: 36-102) were identified from the other 11 HGCAs (Figure 1A, Supplementary Table 2 and Supplementary Table 3). The C: G->T: A transitions were the most significant changes in the HGCA samples (Figure 1B and Supplementary Table 2), which was consistent with a previous report that analyzed a colon adenoma [13]. Based on the notion that DNA methylation frequently occurs within the context of CpG sites, the enrichment of C: G->T: A transitions in 5′-CpG-3′ dinucleotides might be related to extensive DNA methylation at 5′-CpG-3′ sites in CRC tumorigenesis [14, 15].…”
Section: Resultssupporting
confidence: 91%
“…Excluding this hypermutated HGCA, a total of 772 somatic non-silent mutations (752 non-synonymous SNVs and 20 indels) (average: 70.2, range: 36-102) were identified from the other 11 HGCAs (Figure 1A, Supplementary Table 2 and Supplementary Table 3). The C: G->T: A transitions were the most significant changes in the HGCA samples (Figure 1B and Supplementary Table 2), which was consistent with a previous report that analyzed a colon adenoma [13]. Based on the notion that DNA methylation frequently occurs within the context of CpG sites, the enrichment of C: G->T: A transitions in 5′-CpG-3′ dinucleotides might be related to extensive DNA methylation at 5′-CpG-3′ sites in CRC tumorigenesis [14, 15].…”
Section: Resultssupporting
confidence: 91%
“…the APC gene at early stage) . In good agreement, recent exome sequencing study conducted by Zhou et al . revealed that APC was mutated in both colorectal adenoma and cancer from the same patients.…”
Section: Discussionsupporting
confidence: 74%
“…This could be due to the fact that neoplastic development in our experiment was limited to precarcinoma stage; whereas, the human exome analyses were performed on stage III colon carcinoma data from TCGA. However, the presence of multiple mutations even at the early adenoma stage has already been confirmed in humans .…”
Section: Discussionmentioning
confidence: 93%